Identifikasi terhadap Pengaruh Disrupsi Teknologi pada Kultur Masyarakat Indonesia yang Islami berdasarkan Framework Digital Quotient - Muhammad Rijal Bagus Hernanda; Indri Sudanawati Rozas; Wiwin Luqna Hunaida (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
This research aims to analyze the influence of digital intelligence on social interaction, especially in the context of Islamic culture in Indonesia in the era of technological disruption. This research uses a literature study method with a qualitative approach, where data is obtained from relevant literature, including journals, books and articles published between 2018 and 2023. Data collection was conducted through Google Scholar with keyword sorting techniques related to Indonesian culture and social interaction. The results show that the development of digital intelligence, especially in the aspect of digital communication, has a significant impact on people's social interactions. Although technology provides convenience in communication, it also contributes to the decline of the values of direct interaction that were previously an integral part of Islamic culture. In addition, new challenges arise in the form of the spread of false information that can affect social harmony. In conclusion, digital intelligence offers solutions for society to adapt to digital life.